2014
DOI: 10.1086/678514
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Hemodynamic Evaluation of Pulmonary Hypertension at Large Referral Centers

Abstract: Despite consensus guidelines for right heart catheterization (RHC) in the diagnosis of pulmonary arterial hypertension (PAH), considerable differences exist in the performance of RHC, interpretation of hemodynamic data, and frequency of RHC performance in patients with established disease. These differences may lead to variability in diagnosis or treatment of PAH. We sought to gather information on the standard practice of RHC for the diagnosis and management of PAH from experienced pulmonary vascular disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Multiple prior investigators-using varied methods including cell and animal models, translational research, and epidemiologic studies-have shown that metabolic conditions such as glucose intolerance, diabetes mellitus, and the metabolic syndrome are closely linked to pulmonary vascular conditions such as PAH and hypoxiamediated PH. [33][34][35][36][37][38][39][40] One prior report on the impact of diabetes mellitus on PAH survival showed increased risk for death, consistent with our findings. 40 Whether intervention on these metabolic processes would mitigate the increase in risk of disease is unknown; although a prior study had been posed (NCT00825266 at clinicaltrials.gov 41 ), no study has been completed.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple prior investigators-using varied methods including cell and animal models, translational research, and epidemiologic studies-have shown that metabolic conditions such as glucose intolerance, diabetes mellitus, and the metabolic syndrome are closely linked to pulmonary vascular conditions such as PAH and hypoxiamediated PH. [33][34][35][36][37][38][39][40] One prior report on the impact of diabetes mellitus on PAH survival showed increased risk for death, consistent with our findings. 40 Whether intervention on these metabolic processes would mitigate the increase in risk of disease is unknown; although a prior study had been posed (NCT00825266 at clinicaltrials.gov 41 ), no study has been completed.…”
Section: Discussionsupporting
confidence: 92%
“…There are some important limitations to our study. First , we did not have responses from all CNN and NRN sites, and while this is a common complication of this study design, our overall response rate was comparable with similar studies 24 , 25 . Further, the majority of units that responded had high patient volumes, likely accounting for a large proportion of cPH‐related practices within the network.…”
Section: Discussionmentioning
confidence: 80%
“…First , we did not have responses from all CNN and NRN sites, and while this is a common complication of this study design, our overall response rate was comparable with similar studies. 24 , 25 Further, the majority of units that responded had high patient volumes, likely accounting for a large proportion of cPH-related practices within the network. Second , while CNN includes all tertiary centers in Canada, NRN is one of the several major neonatal networks existing in the United States and may not reflect management practices on a national scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurement of left ventricular end-diastolic pressure may also be warranted ( 5 ). Precision in hemodynamic evaluation and reporting is crucial because the RHC operator is commonly not the treating provider, and even at experienced PH centers, only 50% of the clinicians will subsequently review the hemodynamic tracings themselves ( 6 ). Melillo and colleagues are to be congratulated given the clinical relevance of their findings.…”
mentioning
confidence: 99%